The Praiseworthiness of Divine Beauty – The 'Shaykh al-Hind' Maḥmūd al-Ḥasan, social justice, and Deobandiyyat. Issue 4 (1st October 2016) - Hartung, Jan-Peter
ABSTRACT: In this article, two threads of scholarship on the relationship of what shall be called here the 'Deoband project' and politics are negotiated. Both these threads frame this relationship in absolute terms: one considers Deoband as a politically neutral yet rather homogeneous 'movement' for the reform of religious beliefs and practices, while the other cast it in a similar monolithic fashion as an anti-colonial champion of social justice. Against this mutual exclusiveness, it is argued here that a revised understanding of what 'Deoband' constitutes and stands for will help to show that, although it did not often make a politics explicit, embedded in a genealogy of the 'Deoband project' as a phenomenon is an activist iteration of Sufism, one that developed in dialogue between classes in the stratified semi-urban milieus of the imperial heartland around Deoband, and South Asian rural peripheries. In the early twentieth century, this conversation developed into what is idealtypically framed here as 'Islamic Pietism'. All this is argued through a survey of the literature surrounding one of Deoband's least-documented, yet possibly most famous, scholars: Maḥmūd al-Ḥasan, commonly known as 'Shaykh al-Hind'. In narrating 'Islamic Pietism' across Maḥmūd al-Ḥasan's life, but also his milieu and the careers of his compatriots, not only a major gap in the historical research of contemporary South Asian Islam is addressed. More so, it is highlighted how even renowned individual actors were constituted by cross-class and multi-scalar networks of thought and agency – almost as much as they disproportionately transformed them.